Recent Advancements on Benzimidazole: A Versatile Scaffold in Medicinal Chemistry - Alzhrani, Zohor M. M.; Alam, Mohammad M.; Nazreen, Syed (Mini Reviews in Medicinal Chemistry, 2022)
Abstract: Benzimidazole is a nitrogen-containing fused heterocycle which has been extensively explored in medicinal chemistry. Benzimidizole nucleus has been found to possess various biological activities such as anticancer, antimicrobial, anti-inflammatory, antiviral, antitubercular and antidiabetic. A number of benzimidazoles such as bendamustine, pantoprazole have been approved for the treatment of various illnesses, whereas galeterone and GSK461364 are in clinical trials. The present review article gives an overview of the different biological activities exhibited by the benzimidazole derivatives as well as different methods used for the synthesis of benzimidazole derivatives in the past ten years.
Keywords: Benzimidazole